Elementary School Teachers’ Competencies: In-Service Teachers Training Model for Content, Culture, Technology Integration - Riastini, Putu Nanci; Mahayanti, Ni Wayan Surya; Dharmayanti, Putu Ari; Widiartini, Ni Ketut; Tuilan, Jeane; Mukminin, Amirul (Journal of Ecohumanism, 2024)
Teachers’ competencies, in terms of content, culture, and technology, are the main capital for managing 21st-century learning. Despite the importance, these competencies have not been well developed, specifically at the elementary level, indicating the pressing need to develop a training model. Therefore, this study aims to develop a quality INSET CULTECH model for in-service teachers that integrates content, culture, and technology. The study procedures were carried out using a Four-D development method. The training model was content-validated by experts and responses were received from teachers before testing with repeated measurement. The sample population comprised teachers from public elementary schools in Denpasar City. In addition, competencies data before and after participating in INSET CULTECH were analyzed using Repeated Measure ANOVA. The results showed that the quality of the training model developed was in a good category. This study is expected to have an impact on developing competencies in integrating Balinese culture into basic science learning, using mobile technology, and implementing innovative learning with the developed media.